Biological treatment of wastewater polluted with an oxyfluorfen-based commercial herbicide. (December 2018) - Carboneras, María Belén; Villaseñor, José; Fernández-Morales, Francisco Jesús; Rodrigo, Manuel Andrés; Cañizares, Pablo
Abstract: Fluoxil-24 is a commercial herbicide based on oxyfluorfen (a hazardous non-soluble organochlorinated compound) and additional compounds used as solvents. The aim of this work is to study the biotreatability of this commercial herbicide in water through batch experiments performed at different temperatures (15, 20, 25 and 30 °C) and initial concentrations (85, 150, 300 and 500 mg L −1 of oxyfluorfen). Activated sludge from an oil refinery wastewater treatment plant was acclimated and used for biodegradation experiments. Two main mechanisms, volatilization and biodegradation, were observed to be responsible of the herbicide removal. Fluoxil-24 removal efficiencies between approximately 40% and 80% were reached after 70 h, depending on the conditions used, and oxyfluorfen was not completely removed. Regarding the influence of the temperature, thermal inhibition problems appeared at 30 °C, and the volatilization rate of solvents increased, causing oxyfluorfen to become unavailable for microorganisms. An increase of herbicide initial concentration did not clearly affect the herbicide removal efficiency, whereas it negatively affected the biological mechanism. The experimental results were fitted to a mathematical model that included both simultaneous mechanisms of volatilization and Monod biodegradation kinetics. The model was able to predict the experimental results, and the calculated model parameters confirmed the effect of the variables under study. Graphical abstract: Highlights: Acclimated microbial culture was able to biodegrade oxyfluorfen-based herbicide. Simultaneous volatilization and biodegradation affected biotreatment performance. Initial herbicide concentration did not clearly affect the process efficiency. High temperatures affected hardly biodegradation due to volatilization of solvents.